Main Risk Factors for Cardiovascular Diseases - Mutabar Abduganievna Mirpaizieva (Scholars Digest Publishing, 2024)
Cardiovascular disease (CVD) is the leading cause of death worldwide, and people with or at high risk of CVD require early detection and care. Most cardiovascular diseases can be prevented by addressing risk factors such as unhealthy diet and obesity, physical inactivity, tobacco use, physical inactivity and harmful.
Keywords: cardiovascular morbidity, risk factors, coronary heart disease, primary health care, prevention.